Critical Thinking Ability of Junior High School Students Who Have Self-Confidence - Mulyani, Sari; Hidayati, Herlina; Muttaqien, Anwar (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
Students often have difficulty in solving problems, this is due to lack of confidence and students' critical thinking skills are still low. Critical thinking skills are needed to make decisions in solving problems on problems. In order for students to make decisions, students must have confidence in practicing critical thinking skills. This study aims to describe students' critical thinking skills in solving story problems in junior high school students who have confidence. This research method is descriptive research with a qualitative approach, in the form of the results of the work of non-test students, written tests and in-depth interviews. This study included 2 subjects who had the ability to think critically with confidence. The results of this study show that students can meet all criteria such as (1) students are able to understand problems, write down problem information from known, namely Tini bought 2 pens and bought 1 writing book, while Aisyah bought more pens than Tini equivalent to the price of books, then what was asked was the price of 2 pens and 3 writing books, respectively, (2) students are able to analyze and create mathematical models, able to consider assumptions and determine the results of completion, namely solving mathematical models on the material of a system of two-variable linear equations (SPLDV). And (3) students are able to draw conclusions from the problem, namely being able to conclude from the results of the final solution correctly. So that students are able to understand, model and solve problems appropriately.